Serum Procalcitonin Levels in Acute Encephalopathy with Biphasic Seizures and Late Reduced Diffusion. (14th March 2018) - Fujii, Yosuke; Yashiro, Masato; Yamada, Mutsuko; Kikkawa, Tomonobu; Nosaka, Nobuyuki; Saito, Yukie; Tsukahara, Kohei; Ikeda, Masanori; Morishima, Tsuneo; Tsukahara, Hirokazu
Abstract : Procalcitonin (PCT) is used as a biomarker in severe infections. Here, we retrospectively investigated levels of serum PCT, C-reactive protein (CRP), and inflammatory cytokines (IL-6, TNF- α, and IFN- γ ) in the second phase of patients with acute encephalopathy with biphasic seizures and late reduced diffusion (AESD). Nine AESD pediatric patients (4 men, 5 women; AESD group) admitted to Okayama University Hospital from 2010 to 2016 were compared with 10 control patients with febrile seizures (FS) (3 men, 7 women; FS group). Mean PCT concentrations (ng/mL) in the AESD and FS groups were significantly different, at 9.8 ± 6.7 and 0.8 ± 0.9, respectively (p = 0.0006 ). CRP (mg/dL) were 0.79 ± 0.89 and 1.4 ± 1.0 (p = 0.94 ), respectively; IL-6 (pg/mL) were 449.7 ± 705.0 and 118.3 ± 145.4 (p = 0.20 ), respectively; TNF- α (pg/mL) were 18.6 ± 12.5 and 16.6 ± 6.0 (p = 0.67 ), respectively; and IFN- γ (pg/mL) were 79.6 ± 158.5 and 41.9 ± 63.7 (p = 0.56 ), respectively. Ratios of PCT to CRP were 27.5 ± 34.2 and 3.2 ± 6.8 (p < 0.0001 ), respectively. The sensitivity and specificity in the diagnosis of AESD using a cutoff of PCT/CRP ratio of 1.0 were 79% and 100%, respectively. These results suggest that PCT and the PCT/CRP ratio are useful in auxiliary diagnosis of the second stage of AESD, and in AESD, PCT is likely to increase through a different mechanism.